Publicidad en medios televisivos y hábitos alimenticios - Delgado Hidalgo, Adrin Ronald (2023)
The research project entitled "Influence of the paid mentions or advertising brands of the morning program En Contacto in the eating habits of the students of the UNIDAD EDUCATIVA FISCAL SARAH FLOR JIMENEZ, is created with the purpose of analyzing how influential are the speeches used to advertise the paid mentions or products presented in the program. To obtain this information, field research was used in which the qualitative and quantitative research method was employed with the use of survey and interview techniques. With the results we proceeded to the analysis of tables and graphs, After the analysis we proceeded to present the proposal through an account on the social network Instagram to promote a nutritious choice.